Hydrolysis of Ammonia-Borane over Ni/ZIF-8 Nanocatalyst: High Efficiency, Mechanism, and Controlled Hydrogen Release - Wang, Changlong (2017)
Non-noble metal nanoparticles are notoriously difficult to prepare and stabilize with appropriate dispersion, which in turn severely limits their catalytic functions. Here, using zeolitic imidazolate framework (ZIF-8) as MOF template, catalytically remarkably efficient ligand-free first-row late transition-metal nanoparticles are prepared and compared. Upon scrutiny of the catalytic principles in the hydrolysis of ammonia-borane, the highest total turnover frequency among these first-row late transition metals is achieved for the templated Ni nanoparticles with 85.7 molH2 molcat -1 min-1 at room temperature, which overtakes performances of previous non-noble metal nanoparticles systems, and is even better than some noble metal nanoparticles systems. Mechanistic studies especially using kinetic isotope effects show that cleavage by oxidative addition of an O-H bond in H2O is the rate-determining step in this reaction. Inspired by these mechanistic studies, an attractive and effective "on-off" control of hydrogen production is further proposed.